Le travail de l’os, de la corne et de l’ivoire animaux au cours des premiers siècles du haut Moyen Âge. Quelques exemples de nouvelles productions du royaume franc - Paolo de Vingo (Archéologie Médiévale)
The considerable amount of bone items discovered in early medieval settlements and grave contexts suggests that the working of vertebrate bones, antlers from hoofed mammals, bovine horn and mammal teeth does not represent minor productions, but rather an important sector of economic activity. The use of bone in the early Middle Ages arises from the craftwork traditions of the late Roman period, from which we can learn about production techniques. The enquiry centres on the precise identification of the raw materials from which the discs and counters, dice and chess pieces, small object cases, sword pommels and knife handles, combs, hair pins and belt buckles were made. Identification may also shed light on commercial supply channels, or reveal the existence of production based solely on local resources. In the latter case, the raw materials were linked to hunting and gathering practices. The amount of items produced was not only related to the demand from local markets, but also to the supply of raw materials.